Implications of Islamic Education in The Era of The Kalifah Umar bin Khattab in Building Islamic Civilization - Syukur, Syamsiar (Al-Hikmah, 2023)
The aim of this research is to determine the implications of Islamic education during the time of Caliph Umar bin Khattab (624-644 AD) in building Islamic civilization. Khalidfa Umar was an intellectual and mujaddid of the classical era. During his time, Islamic government experienced transformation and great leaps through innovation, political reform and ideas in the nature of modern ijtihad; about law and fiqh, social society, religious moderation and others. Another character of Caliph Umar was his hobby of doing blusukan. The characters above show that Umar is a leader who is out of the box. The contribution of education during the time of Umar bin Khattab to the progress of Islamic civilization was at least through several of its policies, including (1) sending teachers or Islamic intellectuals with madrasas or halaqahs to all Islamic territories, from these madrasas producing new intellectuals in large numbers. (2) ordered the Islamic commander who conquered the territory to establish a mosque as an Islamic Center which would be used as a center for Islamic activities, namely as a place of worship and as a place for educational processes. Apart from that, Umar’s rational characteristics and tradition of understanding texts using a textual approach have influenced the rationalistic thinking of subsequent Islamic intellectuals - some of whom contributed to the peak progress of Islamic civilization, especially during the Abbasid dynasty in Baghdad and the Fatimid dynasty in Egypt.